Exploring Male Partners and Health Workers’ Views on Women’s Utilisation of Maternal Healthcare Services in Bauchi State, Nigeria - Azi, Hadiza Y.; Redwood, Tracey; Spencer, Melinda (British Journal of Healthcare and Medical Research, 2025)
Healthcare services at Maternal healthcare facilities operate to provide safe delivery for women of childbearing age. The numerous maternal deaths remain a concern, even though the government maintains maternity healthcare facilities. All literature studies show that health services usage remains low in rural regions, particularly Northern Nigeria. This study delved into exploring male partners' and health workers' views on women's utilisation of maternal healthcare services in Bauchi state, Nigeria. The study adopted a case study qualitative research design. A purposive sampling technique was used to select five married men and two skilled birth attendants, who were interviewed using a semi-structured interview guide. The data collected were transcribed and translated from Hausa to English. Braun and Clarke's (2006) Thematic Data Analytical technique was used to analyse the data with Computer-Assisted Qualitative Data Analysis Software (CAQDAS), MAXQDA 2024. Three themes emerged from the analysis: maternal healthcare factors, women's use of maternal healthcare, and women's issues. There was a staff shortage, an unfavourable staff attitude, and a distance from the health centres. In contrast, the maternal healthcare centres were not in good condition to attract reproductive women to the healthcare centre. Reproductive women experienced financial challenges and inadequate spousal support and mostly used healthcare during emergencies. Hence, it was recommended that health institutions, NGOs, and policymakers should partner to educate communities about home and self-delivery, including the potential risks and benefits